The Psychometric Properties of the Norwegian version of Autism Diagnostic ObservationSchedule, Second Edition (ADOS-2) - Brøndbo, Per Håkan; Høyland, Anna Lise (PsykTestBarn, 2018)
Description: The Autism Diagnostic Observation Schedule, Second Edition (ADOS-2)(Lord, et al., 2012) was designed to assess and diagnose autism spectrum disorders (ASDs) across developmental levels, language skills, and age The ADOS-2 was developed by Lord et al. and is a revised version of the original ADOS-G (Lord, et al., 2000). The revision includes new and revised algorithms for the modules 1 – 4 and a Toddler Module intended for children between 12 and 30 months of age, who do not consistently use phrase speech (Hus & Lord, 2014). This means that the ADOS-2 can be used with a wide range of individuals; from one-year-olds with no speech to adults. The included severity scales facilitate comparisons across the different modules. The test, which comprises five modules, five Protocol Booklets and a manual, was translated into Norwegian by Synnve Schölberg, Kenneth Larsen and Niels Petter Thorkildsen in 2014. Proper administration of the test requires adequate knowledge of both the test and ASDs; e.g., clinicians who have received special training. Copyright © 2012 Western Psychological Services, Högrefe Psykologiforlaget AB © has the Norwegian translation rights. The administration of the ADOS-2 takes approximately 40 to 60 minutes. The scores are based on all tasks across the test, and the algorithms are closely related to the diagnostic criteria. Literature search: The systematic search yielded 67 Norwegian articles, none of which met the inclusion criteria. An equivalent search resulted in 129 Scandinavian articles, three of which met the inclusion criteria. In addition, one Norwegian article was included, following the suggestion of the Scandinavian main authors. All four included articles reported results of cross-sectional studies; three of which were clinical studies. The fourth article reported data from a Norwegian population-based study. Psychometrics: Prevalence and mean results were reported in the Norwegian study. The diagnostic validity was examined in both the Norwegian and the Swedish version. In addition, the reliability was examined in a Swedish study. Norwegian or Scandinavian norms were not available. We examined the psychometric properties of the ADOS-2 reported in four Scandinavian studies. Conclusion: Since the documentation was limited, we advise that the instrument should be employed with caution, and suggest following the recommendation of the ADOS-2 manual to use additional tests and supplemental clinical information when making an ASD diagnosis.